High-Temperature Rutting Resistance of Inverted Asphalt Pavement Structure - Yingjun Jiang; Yu Zhang; Changqing Deng; Yong Yi; Tian Tian; Kejia Yuan (Advances in Civil Engineering)
To improve the high-temperature rutting resistance of asphalt pavements, an inverted asphalt pavement structure (IAPS), 4 cm AC-13 mixture + 8 cm AC-25 mixture + 6 cm AC-20 mixture + 54 cm cement-stabilized macadam, was proposed herein by considering engineering practice, theoretical calculation, and analysis. A rutting prediction equation of asphalt pavements was then proposed via rut-development trends found by laboratory 18 cm thick rutting test. Subsequently, the rutting resistance of the IAPS was evaluated. The results show that, compared with the traditional asphalt pavement structure (TAPS), 4 cm AC-13 mixture + 6 cm AC-20 mixture + 8 cm AC-25 mixture + 54 cm cement-stabilized macadam, the maximum shear stress of the IAPS can be reduced by ∼1.7% along with improvements in rutting resistance by ∼16% and ∼12% under wheel loads of 0.7 and 1.2 MPa, respectively. Wheel-load increase affects the rutting resistance of both structures in a similar manner: when the wheel load increases from 0.7 MPa to 1.2 MPa, the rut depths of both pavement structures increase by at least 63%. The IAPS clearly has better rutting resistance than the TAPS and is thus the better choice for asphalt pavement structure design.